Development of fibroblast activation protein-targeted radiotracers with improved tumor retention - Loktev, Anastasia; Lindner, Thomas; Altmann, Annette; Giesel, Frederik L.; Kratochwil, Clemens; Debus, Jürgen; Marmé, Frederik; Jäger, Dirk; Mier, Walter; Haberkorn, Uwe (Journal of nuclear medicine, 2019)
Cancer-associated fibroblasts constitute a vital subpopulation of the tumor stroma and are present in more than 90% of epithelial carcinomas. The overexpression of the serine protease fibroblast activation protein (FAP) allows a selective targeting of a variety of tumors by inhibitor-based radiopharmaceuticals (FAPIs). Of these compounds, FAPI-04 has been recently introduced as a theranostic radiotracer and demonstrated high uptake into different FAP-positive tumors in cancer patients. To enable the delivery of higher doses, thereby improving the outcome of a therapeutic application, several FAPI variants were designed to further increase tumor uptake and retention of these tracers. Methods: Novel quinoline-based radiotracers were synthesized by organic chemistry and evaluated in radioligand binding assays using FAP-expressing HT-1080 cells. Depending on their in vitro performance, small-animal PET imaging and biodistribution studies were performed on HT-1080-FAP tumor-bearing mice. The most promising compounds were used for clinical PET imaging in 8 cancer patients. Results: Compared with FAPI-04, 11 of 15 FAPI derivatives showed improved FAP binding in vitro. Of these, 7 compounds demonstrated increased tumor uptake in tumor-bearing mice. Moreover, tumor-to-normal-organ ratios were improved for most of the compounds, resulting in images with higher contrast. Notably two of the radiotracers, FAPI-21 and -46, displayed substantially improved ratios of tumor to blood, liver, muscle, and intestinal uptake. A first diagnostic application in cancer patients revealed high intratumoral uptake of both radiotracers already 10 min after administration but a higher uptake in oral mucosa, salivary glands, and thyroid for FAPI-21. Conclusion: Chemical modification of the FAPI framework enabled enhanced FAP binding and improved pharmacokinetics in most of the derivatives, resulting in high-contrast images. Moreover, higher doses of radioactivity can be delivered while minimizing damage to healthy tissue, which may improve therapeutic outcome.
Gesehen am 28.10.2019